Genetic mapping and genome-wide association study identify BhYAB4 as the candidate gene regulating seed shape in wax gourd (Benincasa hispida) - Luo, Chen; Yan, Jinqiang; Liu, Wenrui; Xu, Yuanchao; Sun, Piaoyun; Wang, Min; Xie, Dasen; Jiang, Biao (Frontiers in Plant Science, 2022)
Wax gourd is an important vegetable crop of the Cucurbitaceae family. According to the shape and structure of the seed coat, the seeds of wax gourd can be divided into bilateral and unilateral. Bilateral seeds usually germinate quickly and have a high germination rate than unilateral seeds. Thereby, wax gourd varieties with bilateral seeds are more welcomed by seed companies and growers. However, few studies have reported the seed shape difference in wax gourd. In this study, genetic analysis demonstrated that the seed shape of wax gourd was controlled by a single gene, with bilateral dominant to unilateral. Combined with genetic mapping and genome-wide association study, Bhi04G000544 (BhYAB4), encoding a YABBY transcription factor, was identified as the candidate gene for seed shape determination in wax gourd. A G/A single nucleotide polymorphism variation of BhYAB4 was detected among different germplasm resources, with BhYAB4G speciﬁcally enriched in bilateral seeds and BhYAB4A in unilateral seeds. The G to A mutation caused retained intron and premature stop codon of BhYAB4. Expression analysis showed that both BhYAB4G and BhYAB4A were highly expressed in seeds, while the nuclear localization of BhYAB4A protein was disturbed compared with that of BhYAB4G protein. Finally, a derived cleaved amplified polymorphic sequence marker that could efficiently distinguish between bilateral and unilateral seeds was developed, thereby facilitating the molecular marker-assisted breeding of wax gourd cultivars.